Control of Host‐Matrix Morphology Enables Efficient Deep‐Blue Organic Light‐Emitting Devices. Issue 12 (9th February 2023) - Zhao, Haonan; Kim, Jongchan; Ding, Kan; Jung, Mina; Li, Yongxi; Ade, Harald; Lee, Jun Yeob; Forrest, Stephen R.
Abstract: Mixing a sterically bulky, electron‐transporting host material into a conventional single host–guest emissive layer is demonstrated to suppress phase separation of the host matrix while increasing the efficiency and operational lifetime of deep‐blue phosphorescent organic light‐emitting diodes (PHOLEDs) with chromaticity coordinates of (0.14, 0.15). The bulky host enables homogenous mixing of the molecules comprising the emissive layer while suppressing single host aggregation; a significant loss channel of nonradiative recombination. By controlling the amorphous phase of the host‐matrix morphology, the mixed‐host device achieves a significant reduction in nonradiative exciton decay, resulting in 120 ± 6% increase in external quantum efficiency relative to an analogous, single‐host device. In contrast to single host PHOLEDs where electrons are transported by the host and holes by the dopants, both charge carriers are conducted by the mixed host, reducing the probability of exciton annihilation, thereby doubling of the deep‐blue PHOLED operational lifetime. These findings demonstrate that the host matrix morphology affects almost every aspect of PHOLED performance. Abstract : Mixing a sterically bulky, electron‐transporting host material into a conventional single host–guest emissive layer is demonstrated to suppress phase separation of the host matrix while increasing the efficiency by 120% and the operational lifetime of deep‐blue phosphorescent organic light‐emitting diodes with chromaticity coordinates of (0.14, 0.15).